Absence of the c.169+50delTAAACAG mutation of SOD1 gene in a sample of keratoconus patients in Brazilian population - Lopes, Alessandro Garcia [UNESP]; De Almeida Júnior, Gildásio Castello; Teixeira, Ronan Marques [UNESP]; De Mattos, Luiz Carlos; Brandão De Mattos, Cinara Cássia; Castiglioni, Lilian [UNESP] (Springer Nature, 2020)
Objective: To determine the presence of the 7-bp deletion c.169+50delTAAACAG in intron 2 of Superoxide Dismutase-1 gene in keratoconic patients from the State of São Paulo, Brazil, which promotes splicing variations, resulting in non-functional Superoxide Dismutase-1 antioxidant proteins, which may damage the corneal structure. Results: A group of 35 keratoconic patients, from whom 35 peripheral blood samples and 58 samples of corneal fragments were evaluated, and a control group of 89 individuals, from whom 41 blood samples and 149 samples of corneal fragments were collected. After the amplification of DNA fragments by polymerase chain reaction, mutational screening analysis was performed by enzymatic digestion, followed by direct sequencing. The absence of the 7-bp c.169+50delTAAACAG mutation in intron 2 of Superoxide Dismutase-1 gene was detected in the analyzed subjects of the 2 groups, both in the cornea and peripheral blood samples. Then, according to our results, there is no involvement of c.169+50delTAAACAG deletion in the pathogenesis of keratoconus in this population, once it was not detected. But we emphasize that studies involving this deletion must be continued in an attempt to elucidate this issue.
Keywords: Cornea; Corneal Diseases; Genetic; Keratoconus; Polymorphism; Superoxide Dismutase-1 gene